Obra literaria “Blanca Nieves y los Siete Enanitos” - Llivi Ruilova, Danny Vicente (2024)
Students of the first parallel cycle “A” of the Disaster Risk Engineering career of the Faculty of Health and Human Sciences of the UEB, presented the literary work “Snow White and the Seven Dwarves” an academic cultural and social event ; under the tutelage of Mgtr. Ruth Cecibelt Cedeño Álvarez, teacher of the subject of Oral and Written Expression.